Implementation Of Religious Moderation In Islamic Educational Institutions (Case Study At MTI Pariangan) - Riri Susanti; Darwati, Darwati (Cita konsultindo, 2023)
Until now, the tendency of intolerance with all forms of action in society has not diminished, on the contrary, it has strengthened. Some of the research conducted shows that radical groups spread their views massively through educational institutions, where students, university students and teachers are the target objects, even social media. Intolerance and radicalism in the name of religion tend to be bigger than ethnic reasons. The general aim of this research is to examine the development of religious moderation in MTI Parianagan. Specifically, the study is directed at: 1) The concept of religious moderation according to the view of MTI Pariangan; 2) The practice of religious moderation at MTI Pariangan; and 3) Factors that influence the understanding of the concept and practice of religious moderation at MTI Pariangan. This qualitative research method will be carried out in 2022 at MTI Pariangan. On the other hand, religious education institutions, especially at MTI Pariangan, have a very important function and role in sowing the principle of religious moderation, and even become a laboratory of religious moderation. Students need to be given a very adequate understanding of the nature of the various differences of human beings in their various dimensions, both in the context of social and national life. So the mainstreaming of the principle of religious moderation through the participation of religious education institutions is very strategic.